Teachers’ Understanding of the Deep Learning Approach in Teaching Practices at Vocational High Schools: A Case Study at SMK Al-Fathiyah, Jakarta - Fajar Wahyudi Utomo; Ajeng Ginanjar; Muhammad Ilman Naafi'a (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study explores teachers’ understanding of the deep learning approach within the context of vocational education in Jakarta. Using a descriptive qualitative design supported by survey data and interviews, the research examines how teachers conceptualize, plan, and implement deep learning principles in their everyday instructional practices. The findings indicate that teachers generally possess a foundational awareness of deep learning and demonstrate efforts to apply learner-centered strategies, authentic assessment, and reflective facilitation. However, the depth and consistency of implementation vary across individuals, pointing to the need for more structured professional development. The study highlights the importance of strengthening pedagogical knowledge, enhancing instructional design, and enriching assessment literacy to support meaningful learning. The results contribute to ongoing discussions on improving teaching quality in vocational schools through deeper, more transformative learning experiences.